Struggles for multilingualism and linguistic citizenship - Williams, Quentin (Multilingual matters, 2022)
This book offers a fresh perspective on the social life of multilingualism through the lens of linguistic citizenship. Each chapter illuminates how multilingualism (in both theory and practice) should be, or could be, thought of as inclusive when we recognize what multilingual speakers do with language for voice and agency